Legal Protection For Children Who Perform Underage Marriages According To Law Number 35 Of 2014 Concerning Child Protection - Nasir, Citra; Ichsan , Nursyamsi; Heriyanto, Heriyanto; Abbas, Abbas (Universitas Pahlawan Tuanku Tambusai, 2022)
Determining the age limit for marriage is very important because every bride and groom must have biological and psychological maturity. Referring to KPPPA data at the end of last year, in just one day there are 375 children under the age of 18 who carry out marriages and in the Marriage Law there is a dispensation with parental consent. The purpose of this study is to determine the extent of child protection in the Protection Law with normative legal research methods. The results of the study are legal protection for children to prevent underage marriage, including a) Juridical child protection which in the Child Protection Law has applied sanctions for parties involved in underage marriage, either directly or indirectly has violated children's rights, although its implementation cannot be realized optimally if it is not accompanied by awareness from parents and children themselves. Whereas, b) Non-juridical child protection: The reason for child protection to prevent underage marriage is very important because it will result in education, association and environment, health, psychology and especially prevent the increase in divorce rates.